Student perceptions of the hybrid learning practicum Qualitative Analysis Protein based Constructivism Needham's 5-phase - Diah Kartika Sari; Made Sukaryawan; Sofia Sanjaya; Eka Ad'hiya; Annisa Nurjannah; Mega Wulandari (Jurnal Penelitian Pendidikan IPA, 2022)
This study aims to determine student perceptions of hybrid learning practicum on the topic of qualitative analysis protein-based constructivism Needham's 5-phase. This study uses a quantitative descriptive method. Perception assessment is carried out by referring to 3 dimensions of perception consisting of 4 perception indicators, namely Perception of lecturers, perception of the teaching and learning process, perception of the social environment, and perception of assessment. Data was collected using online questionnaires via google form to students taking biochemistry practicum courses using purposive sampling technique. The results showed that the perception of lecturers obtained a perception level of 74%, the perception of the teaching and learning process was 79%, the perception of the social environment was 81%, and the perception of the assessment was 78%. The percentage of the average perception level was 78%, indicating the feasibility or success of the hybrid learning practicum of qualitative analysis protein based on Needham's five-phase constructivism. Overall, it can be concluded that students' perceptions of the hybrid learning practicum on the topic of qualitative analysis protein based on constructivism Needham's five-phase got the level of perception in the good category